STRATEGI KADER BINA KELUARGA BALITA (BKB) DALAM OPTIMALISASI FUNGSI EDUKASI KELUARGA - Mutiara Mahar Dwinandia; Muhammad Irfan Hilmi (IKIP Siliwangi, 2022)
The research reveals how the strategy of “Bina Kelurga Balita” cadre (BKB) in optimizing the function of family education at BKB Amarilis Lembang, Jawa Barat. This study uses a qualitative approach with a descriptive method. Data collection techniques are observation, interviews, documentation studies, and literature studies. The selection of research informants used purposive sampling technique. Research informants were the chairman of BKB, BKB cadres, and members of BKB. Data analysis using the Miles and Huberman model includes the steps of data collection, data reduction, data presentation/data display, conclusion drawing and verification. The results of the research on the strategy used by BKB cadres, namely the bottom up strategy through counseling, BKB cadres provide guidance to BKB members regarding parenting by using a participatory approach. Activity planning is carried out by carrying out the identification of needs and potentials, formulation of objectives, selection of program targets. The material presented is about child development because parents feel that child development is very important in optimizing children's potential.